Very High Resolution Ultrasound Imaging for Real-Time Quantitative Visualization of Vascular Disruption after Spinal Cord Injury - Soubeyrand, Marc (Mary Ann Liebert, Inc., 2014)
Spinal cord injury (SCI) is characterized by vascular disruption with intramedullary hemorrhage, alterations in blood-spinal cord barrier integrity, and perilesional ischemia. A safe and easily applied imaging technique to quantify evolving intraspinal vascular changes after SCI is lacking. We evaluated the utility of very high resolution ultrasound (VHRUS) imaging to assess SCI-induced vascular disruption in a clinically relevant rodent model. The spinal cords of Wistar rats were lesioned at the 11th thoracic vertebra (Th11) by a 35 g 1-minute clip compression. Three-dimensional quantification of intraspinal hemorrhage using VHRUS (at an acute 90-min and subacute 24-h time point post-SCI) was compared with lesional hemoglobin and extravasated Evans blue dye measured spectrophotometrically. The anatomy of hemorrhage was comparatively assessed using VHRUS and histology. Time-lapse videos demonstrated the evolution of parenchymal hemorrhage. VHRUS accurately depicted the structural (gray and white matter) and vascular anatomy of the spinal cord (after laminectomy) and was safely repeated in the same animal. After SCI, a hyperechoic signal extended from the lesion epicenter. Significant correlations were found between VHRUS signal and hemorrhage in the acute (r=0.88, p<0.0001) and subacute (r=0.85, p<0.0001) phases and extravasated Evans blue (a measure of vascular disruption) in the subacute phase (r=0.94, p<0.0001). Time-lapse videos demonstrated that the expanding parenchymal hemorrhage is preceded by new perilesional hemorrhagic foci. VHRUS enables real-time quantitative live anatomical imaging of acute and subacute vascular disruption after SCI in rats. This technique has important scientific and clinical translational applications.